2017
DOI: 10.1111/jce.13264
|View full text |Cite
|
Sign up to set email alerts
|

Role of contact force‐guided radiofrequency catheter ablation for treatment of atrial fibrillation: A systematic review and meta‐analysis

Abstract: CF-guided RF catheter ablation was associated with a significant AF/atrial tachycardia-free survival benefit compared with non-CF-guided ablation in patients with paroxysmal AF rather than persistent AF. In addition, CF-guided ablation strategy also reduced the procedure time, fluoroscopy time, as well as RF time despite no distinct effect on the alleviation of procedure-related complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 49 publications
(62 reference statements)
2
20
0
1
Order By: Relevance
“…CF is identified as a key determinant of lesion size, long term ablation efficacy and safety . A Lot's of observational studies have found overwhelming benefit from CF‐guided AF ablation, however a meta‐analysis of randomized data by Virk et al demonstrated that CF guidance does not improve the safety or efficacy of AF ablation . Even though, CF sensing technology in STc enables real‐time monitoring of CF between the catheter tip and tissues, and confirmed persistent appropriate pressure to effectively facilitate RF energy transfer to the tissue .…”
Section: Discussionmentioning
confidence: 99%
“…CF is identified as a key determinant of lesion size, long term ablation efficacy and safety . A Lot's of observational studies have found overwhelming benefit from CF‐guided AF ablation, however a meta‐analysis of randomized data by Virk et al demonstrated that CF guidance does not improve the safety or efficacy of AF ablation . Even though, CF sensing technology in STc enables real‐time monitoring of CF between the catheter tip and tissues, and confirmed persistent appropriate pressure to effectively facilitate RF energy transfer to the tissue .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of CF in creating reliable lesions and improving safety during AF ablation is well documented. 7,10,[12][13][14][15] In the CF group, VT was induced during the procedure in 3 patients (CF value >20 g). In contrast, in the conventional group (in which impedance and temperature-but not CF-were monitored), the ablation procedure had to be suspended because of increasing impedance in 2 patients.…”
Section: Contact Force Value and Ablation Safetymentioning
confidence: 99%
“…Other studies in patients with AF showed that ablation with the CF-sensing catheter improved lesion size and depth and thus improved outcomes. 9,10 However, few studies have investigated the safety and effectiveness of the CF-sensing catheter when used for ablation of premature ventricular contractions (PVCs). 9,11 Therefore, we evaluated whether an irrigated CF-sensing catheter would improve the safety and effectiveness of RFCA of idiopathic PVCs originating from the right ventricular outflow tract (RVOT).…”
mentioning
confidence: 99%
“…9 However, Lin et al performed a recent meta-analysis, demonstrating that this technology facilitates pulmonary vein isolation and results in more favorable outcomes and/or higher rates of AF-free survival without any increase in procedural-related complications. 10 In fact, the overall complication rate for AF ablation appears to be decreasing in comparison with that seen a decade ago. 11 When in doubt, we turn to data.…”
Section: Trouble In Paradisementioning
confidence: 99%